Pengembangan Instrumen Tes untuk Mengukur Kemampuan Berpikir Kritis Siswa pada Materi Tata Surya - Yonatan Vari; Toni Dwi Fauzi (Jurnal Penelitian Pendidikan IPA, 2026)
Industrial Revolution (IR) 4.0 Era required student to develop critical thinking ability.  Indonesian student have a very low ranking PISA in critical thinking ability. The Development of student’s critical thinking need to be done through habituation of learning process to use critical thinking instrument test. Objective of this research is 1) feasibility of critical thinking instrument 2) Measuring students' critical thinking abilities in each indicator of critical thinking abilities developed 3) Instrument quality testing includes difficulty level, discrimination power, and reliability. The development research method used limited to the development stage. It does not reach the full implementation and evaluation stages. This instrument was tested for its feasibility by lecturers and teachers using the Aiken V index, and its quality was tested involving eighth-grade students of SMP Negeri 8 Palangka Raya. The findings obtained in the study include 1) the suitability of the critical thinking instrument for use; 2) Students' critical thinking abilitys are low in each indicator; 3) The quality test shows the need for improvement of the test instrument on 2 questions in the pre-test and 6 questions in the post-test because they have low discriminatory power. This research contributes to outlining the need for instrument quality testing stages in developing critical thinking instruments in addition to the validation stage. Based on the existing findings, it can be concluded that the developed test instrument has undergone improvements based on the validation stage and the instrument quality testing stage used to measure students' critical thinking abilitys on the solar system material, so that it can be a measuring tool that supports the development of science learning that improves students' critical thinking abilitys.